Perfect storm along the neuro-cardiac axis: stroke complicated by acute biventricular dysfunction—Takotsubo syndrome or neurogenic stress cardiomyopathy?. Issue 4 (28th April 2021) - Jackson, Meghan; Nosib, Shravan
Abstract : Acute biventricular dysfunction complicating acute ischaemic stroke poses diagnostic and therapeutic challenges with respect to anticoagulation and short-term and long-term prognosis. We present the uncommon case of an elderly patient presenting with this clinical scenario, who made a full recovery on conservative therapy. Management strategies are discussed and the emerging topic of neuro-cardiac syndromes, namely neurogenic stress cardiomyopathy as distinct from Takotsubo syndrome, is explored.